Relationship Between Front Crawl Trunk Incline and Lower Limbs’ Biomechanics in Non-Expert Swimmers - Mário J. Costa; Marta L. Machado; Paul-Adrien Pserchia; Alain Hamaoui; Catarina C. Santos (Applied Sciences, 2025)
This study examined the relationship between front crawl trunk incline and the lower limbs’ biomechanics in non-expert swimmers. Eighteen male participants (19.22 ± 1.11 years) were recorded in the sagittal plane performing 2 × 25 m of front crawl at maximum intensity to analyze their trunk incline (TI), maximum knee angle (KneeMax), minimum knee angle (KneeMin), knee range of motion (KneeROM), kicking duration (KickDur), descendent phase duration (DurDesc), and ascendant phase duration (DurAsc). They also performed towing for passive drag measurements and a 20 s lower limbs’ tethered test while connected to an electromechanical device and grabbing a floating board to collect the maximum (Fmax) and mean (Fmean) kicking forces. Pearson’s correlation coefficient (r) was used to compute the relationships between all variables. For kinematics, a negative association was found between the TI and v (r = −0.64), KneeMin (r = −0.68), KneeRoM (r = −0.74), and SI (r = −0.52). Regarding kinetics, a single association was found between TI and Fmean (r = −0.52). The results indicate that a greater TI in non-expert swimmers may be a consequence of weaker knee action, which compromises their mean force application and negatively affects velocity and efficiency.